A new species of the genus Seba (Crustacea: Amphipoda: Sebidae) from a cold seep of Mariana Trench - Tokumori, Daigo; Watanabe, Hiromi Kayama; Tanaka, Katsuhiko; Ohara, Yasuhiko; Tomikawa, Ko (Zootaxa, 2025)
A new species of sebid amphipod, Seba marianaensis sp. nov., is described from the Shinkai Seep Field, Mariana Trench, at a depth of 5689–5683 m. Seba marianaensis sp. nov. is most similar to Seba bathybia; however, it differs from S. bathybia by the setation of the mandibular palp and uropod 3 ramus and the shape of the gnathopod 1 coxa. This is the first record of Sebidae from the Mariana Trench.